2020
DOI: 10.1088/2631-8695/ab7683
|View full text |Cite
|
Sign up to set email alerts
|

Effects of melting parameters and quartz purity on silica glass crucible produced by arc method

Abstract: In photovoltaic industry, silica crucible has an important influence on the quality of single crystal silicon. To obtain a silica glass crucible with large diameter, high uniformity, and low bubble content, two series of crucibles were prepared by the arc melting method, one with various melting parameters (initial power, melting power, and melting time) and crucible sizes, and the other with various quartz purities. The bubbles inside the crucible wall and pores on the inner surface were all measured using a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…The total impurity content must be kept below 300 ppm to meet the stringent manufacturing standards for photovoltaics, where such controls are particularly critical. To address these demands, the utilization of high-purity quartz sand as a foundational raw material for quartz crucibles has emerged as an ideal choice, primarily due to its outstanding heat-resistant properties [27]. It is noteworthy that both quartz crucibles and crystalline silicon materials fall within the category of silica-based materials.…”
Section: Photovoltaic Industrymentioning
confidence: 99%
“…The total impurity content must be kept below 300 ppm to meet the stringent manufacturing standards for photovoltaics, where such controls are particularly critical. To address these demands, the utilization of high-purity quartz sand as a foundational raw material for quartz crucibles has emerged as an ideal choice, primarily due to its outstanding heat-resistant properties [27]. It is noteworthy that both quartz crucibles and crystalline silicon materials fall within the category of silica-based materials.…”
Section: Photovoltaic Industrymentioning
confidence: 99%
“…Currently, quartz crucibles are the sole option available to the industry. It has been demonstrated that larger crucibles carry a higher risk of defects, leading to reduced mechanical stability at high temperatures [89].…”
Section: High Demandmentioning
confidence: 99%